레이어링을 사용한 3D 애니메이션 인간형 캐릭터의 감정 표현 방법 제안 - 김주찬(Joo-Chan Kim); 석혜정(Hae-Jung Suk) (한국콘텐츠학회 논문지, 15(5), 2015)
In domestic game market, the video game market is getting smaller and also decreasing funds and high level developers. So we need the software that can help us to make more realistic and high quality contents by non-expert developer in poor environments. In this paper, we selected global studio's animations which were scored good evaluation by public and critics as a well-made emotional expression that can convey the emotion properly. We selected movements that express emotions from the animation scripts by using Ekman's 6 basic emotions and Greimas' dynamic predicate, and then we had analyzed and categorized with the data. We also analyzed the movements for which data we needed to create specific movements to express emotions by using 'Animation Layer' that used in Unity's blending process. And suggest concept of the program that to create the emotional expression movements by using those analyzed data. 국내 게임 업계에서 비디오 게임 시장은 좁아지고 있고 그에 따른 자본과 인력 또한 줄어들고 있다. 이런 열악한 환경과 전문 기술력에서 나오는 콘텐츠의 질적 향상을 위해서는 전문 개발자가 아니더라도 보다 사실적이고 질적으로 뛰어난 콘텐츠를 제작하는 데 도움이 되는 연구가 필요하다. 본 연구에서는 대중과 평론가들에게서 캐릭터 감정 표현 및 전달이 잘 되었다고 평가받는 해외 전문 제작사의 애니메이션들을 선정하였다. 그리고 해당 애니메이션의 스크립트에서 Ekman의 6가지 기본 감정과 그레마스의 역동적 서술어를 이용해 캐릭터가 감정을 표현하는 행동을 선별하여 분석 및 분류하였다. 또한, 게임 제작 프로그램 유니티의 블렌딩 작업에 사용되는 '애니메이션 레이어'를 이용해서 캐릭터가 특정 감정을 표현하려 할 때 필요로 하는 행동들을 분석하고, 이 데이터를 사용해서 감정을 표현하는 행동을 제작해주는 프로그램의 구상안을 제안한다.